2021
DOI: 10.1016/j.ijid.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on HIV care in Guatemala

Abstract: To describe the impact of the coronavirus disease 2019 (COVID-19) pandemic on the diagnosis of human immunodeficiency virus (HIV) and deaths from opportunistic infections in Guatemala. Methods: A retrospective study was conducted to investigate the impact of the COVID-19 pandemic on people with HIV at a referral clinic, as well as the disruption of services at a diagnostic laboratory hub (DLH) which provides diagnosis for opportunistic infections to a network of 13 HIV healthcare facilities. Comparative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
0
17
0
2
Order By: Relevance
“…The findings of other studies also indicated that HIV testing services were reduced during the first season of the COVID-19 pandemic. 10 , 19–21 This could be because government-mandated lockdowns, which are intended to prevent the spread of COVID-19, have had a wide-range impact on health-care delivery. Furthermore, there was widespread public concern about contracting COVID-19 and being diagnosed with the condition, which resulted in a significant drop in VCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of other studies also indicated that HIV testing services were reduced during the first season of the COVID-19 pandemic. 10 , 19–21 This could be because government-mandated lockdowns, which are intended to prevent the spread of COVID-19, have had a wide-range impact on health-care delivery. Furthermore, there was widespread public concern about contracting COVID-19 and being diagnosed with the condition, which resulted in a significant drop in VCT.…”
Section: Discussionmentioning
confidence: 99%
“…The mean difference of HIV PICT also sustained between the years 2019 and 2021. different findings also showed that HIV PICT service was similarly lowered during the first season of the COVID-19 epidemic. 19 , 23 This could be because government-mandated lockdowns, which are intended to prevent the spread of COVID-19, have had a wide-ranging impact on health-care delivery. As a result, COVID-19 infection has had a substantial impact on HIV PICT services.…”
Section: Discussionmentioning
confidence: 99%
“…Although these measures are considered necessary to control the epidemic, they can cause problems inadvertently affecting other public health programs; for example, many non-emergency outpatient clinical services were limited or suspended, many patients were assigned to receive remote treatment, drug supply was disrupted, budgets were reduced, virology laboratory priorities changed and most of their activities were directed toward COVID-19 diagnosis [ 8 ]. Most clinical staff were transferred to COVID-related activities, transportation was restricted, personal mobility was reduced; and generally, all parts of the health care system were affected [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is consistent with other studies. In Guatemala, the diagnostic services for HIV have been severely affected and have increased the deaths from opportunistic infections [ 23 ]. Ethiopia also reported a significant decrease in HIV testing and detection [ 12 ].…”
Section: Discussionmentioning
confidence: 99%